(untitled) (Global Journal of Human-Social Science, 2014)
Naturally ventilated buildings have been observed to be ineffective in warm-humid tropical especially during hot season. To ascertaining this observation, this study presents the results of a shortterm thermal comfort survey performed in a naturally ventilated hostel building in Obafemi Awolowo University, Ile-Ife, Nigeria during hot season. Using the data obtained from questionnaire survey and physical measurement of (air temperature, relative humidity and air velocity) using Kestrel model 4500, thermal environmental conditions, occupant comfort and adaptation methods were investigated considering class II protocol. Ninety six respondents participated in the study. Statistical analysis of students` responses and measured thermal environmental variables was performed to determine existing indoor environmental conditions and priority of using adaptive controls. All the measured environmental variables fell below the comfort range recommended by ASHRAE standard 55 and ISO 7730 standard. On the contrary, respondents were comfortable, preferring cooler, no change environments and more air movement. First preference of the respondents adaptive control was window opening (77.4%), closely followed by wearing light clothes (77.3%) and lastly, the use of electric fans. This study concludes that in warm-humid climate of Ile-Ife, during the hot season the desire for sustainable thermal comfort may not be achieved without mechanical ventilation system.